Alla ricerca di una nuova identità disciplinare. Il fumetto e la transdisciplinarità - Di Paola, Lorenzo (Mediascapes journal, 2019)
Comics - born as a mass medium and then slowly transformed into a niche space in which to experiment and almost predict the media and anthropological forms of the future - is a rich field of investigation to better understand the logic of transmedia narrative and to outline a serious and effective proposal for a study that is truly transdisciplinary. The multimedia nature of comics, which has always been able to anticipate and accompany the methods and forms of the current multimedia communications system (Frezza 1999, 2017) means that today comics are almost a 'permeable membrane' for other sectors of the cultural industry (Jenkis 2006). Indeed, low production costs and a relatively marginal position in the entertainment sector have meant that «l’immaginario su carta è stato ambito di riformulazione radicale dei generi della narrazione visiva e potenzialmente filmica. Dall’ inizio del cinema digitale […] il filo del rapporto tra film digitali e fumetti non si è mai spezzato, si è incrementato esponenzialmente, man mano che le tecnologie digitali si perfezionavano e integravano con quelle tradizionali dei media audiovisivi» (Frezza 2017, 29). This particular nature of comics, which is nurtured precisely by dialogue with other media, however, puts a strain on the efforts of those who would like to frame comics in a certain taxonomy approved by the community of scholars. The institutional weakness and the scarce disciplinary identity of the studies, therefore, depend, on the one hand, on the enigmatic, stratified and multimedia nature of comics, which constantly involves the most diverse disciplines. The strength of studies on the medium, however, lies precisely in the challenge that they can launch to the compartmentalisation of knowledge typical of the academic world, but to do this a truly transdisciplinary shared workspace is indispensable. With this paper, we intend to try to propose a transdisciplinary research practice that rejects a hierarchy of disciplines and that restores the full complexity of the object of analysis, with the hope of helping to define a new and strong disciplinary identity in which the different theoretical approaches and methodologies, far from operating in a blind autonomy, can dialogue and contribute to strengthening studies on the medium.